Effects of peer learning on pupils’ learning performance and creativity in English writing skills using digital storytelling. - A. Shukor, Nurbiha (Penerbit UTM Press, 2022)
Unlimited access to tools can empower learning to greater heights including language learning. Digital storytelling is one of the tools for English Language learning and is widely utilized for better writing skills and learning performance. However, it can also instill creativity in writing which many studies have not explored especially when pupils learn collaboratively to produce a story. This study investigates the effects of peer learning on pupils’ learning performance and creativity in English Writing Skills using digital storytelling. It applied pre-experimental study design in which the same group was given the peer learning treatment using digital storytelling. Participants were 31 pupils aged 11 to 12 years old purposely selected as the samples. This study found that peer learning in digital storytelling has significant effect on pupils’ learning performance in terms of word choice, sentence fluency and conventions and also creativity in writing skills particularly in terms of idea and organisation.